THE TRADITION OF READING LONTARA KUTIKA OF DATARA VILLAGE COMMUNITY, TOMPOBULU DISTRICT GOWA REGENCY (APPRECIATION OF THE AL-QUR’AN VERSES) - Syamhari; Andi Miswar; Nasrum; Sardian Maharani Asnur (Jurnal Adabiyah, 2022)
This research aims to know the tradition of reading Lontara Kutika related to the appreciation of Q.S. Al-Isra:12 in Datara village, Tompobulu district, Gowa regency. This research used descriptive qualitative research using an anthropological approach. Data collection techniques used are observation, interviews, and documentation. The results obtained in the study were the tradition of reading Lontara Kutika was carried out to determine a good time. A good time is applied to every agricultural activity starting from preparation before going to the fields and gardens to work on up to the preparation of the first harvest. The tradition of reading Lontara Kutika is also carried out by the people if they want to determine the time of weddings, banquets and pilgrimage rituals. The timing of the wedding ceremony begins with the timing of the proposal, marriage and the wedding banquet. Meanwhile, determining the good time through the tradition of reading Lontara Kutika at the ritual of the Hajj banquet is carried out in the order of determining when the right time is for the rituals, and determining the time of the rituals for the Hajj. Appreciating Q.S al-Isra: 12 in reading Lontara Kutika in the community of Datara village is a useful activity and is classified as an act that is separated from who did it, because what someone does will be obtained in the future (counted as a reward). The conclusion of the research is that the tradition of reading Lontara Kutika in Datara village community is carried out for the purpose of determining good timing, the texts are read as a reference source of knowledge in determining good timing in various activities of daily life. الملخص تهدف هذه الدراسة إلى تحديد تقليد قراءة Lontara Kutika فيما يتعلق بتقدير Q. آية الأسرة: 12 في تجمع قرية داتارا ، ناحية تومبوبولو ، منطقة جوا. نوع البحث المستخدم في هذا البحث هو بحث نوعي وصفي باستخدام منهج أنثروبولوجي. تقنيات جمع البيانات المستخدمة هي المراقبة والمقابلات والتوثيق. النتائج التي تم الحصول عليها في الدراسة هي تقليد قراءة Lontara Kutika لتحديد الأوقات الجيدة. يتم تطبيق التوقيت المناسب على كل نشاط زراعي بدءًا من التحضير قبل النزول إلى الحقول والحدائق إلى العمل حتى إعداد الحصاد الأول. يتم تنفيذ تقليد قراءة Lontara Kutika أيضًا من قبل المجتمع إذا كانوا يريدون تحديد وقت الزواج والمآدب مثل حفلات الزفاف وطقوس الحج. يبدأ توقيت مراسم الزفاف بتوقيت العرض والزواج ومأدبة الزفاف. وفي الوقت نفسه ، يتم تحديد الوقت المناسب من خلال تقليد قراءة Lontara Kutika في طقوس مأدبة الحج بترتيب تحديد الوقت المناسب للطقوس ، وتحديد وقت طقوس الحج. Q.S التنفيذ آية الإسراء: 12 في قراءة Lontara Kutika في مجتمع قرية داتارا نشاط مفيد ويصنف على أنه فعل منفصل عن الفاعل ، لأن ما يفعله شخص ما سيحصل عليه في المستقبل (يحسب ممارسة ). وخلص البحث إلى أن تقليد قراءة Lontara Kutika في مجتمع قرية داتارا يتم بغرض تحديد التوقيت المناسب ، حيث تُقرأ النصوص كمصدر مرجعي للمعرفة في تحديد الأوقات الجيدة في مختلف أنشطة الحياة اليومية